Rifabutin Use in Staphylococcus Biofilm Infections: A Case Series - James B. Doub; Emily L. Heil; Afua Ntem-Mensah; Renaldo Neeley; Patrick R. Ching (MDPI AG, 2020)
This is a case series of 10 patients who had staphylococcal biofilm infections that were treated with adjuvant rifabutin therapy instead of rifampin therapy. In these cases, rifampin was contraindicated secondary to drug-drug interactions with the patients' chronic medications. Rifabutin therapy was well tolerated with no side effects. As well, no patients had recurrence of their staphylococcal infections. This case series shows that rifabutin can be a beneficial adjuvant therapy in Staphylococcus biofilm infections when drug-drug interactions limit the use of rifampin.